PENGAWASAN DAN TRANSPARANSI DANA DESA ENTIPAN KECAMATAN SEMITAU KABUPATEN KAPUAS HULU - Hahury, Jhony Fredy (Universitas Kapuas Sintang, 2024)
This research seeks to analyse the supervision and transparency of the use of funds in Entipan Village using a qualitative case study approach. The results show that the capacity of village apparatus, community participation, and the use of information technology are key factors in determining the level of transparency and accountability of village fund management. Villages with well-trained apparatus, high community participation, and adoption of information technology show better management of village funds. However, obstacles such as a closed bureaucratic culture and resistance to change remain key challenges. Recommendations include improving the capacity of the apparatus through training, increasing community participation, and adopting information technology to support transparency and accountability. With these measures, it is expected that the management of village funds can be better and support sustainable development at the village level.